Peran Bank Syariah dalam Menghadapi Ketidakpastian Kebijakan Geopolitik dan Ekonomi: Studi dari Negara-negara OKI - Nani Suhartini; Mohamad Ainun Najib; Dahlia Bonang (CV. ITTC INDONESIA, 2026)
The increasing global geopolitical tensions, economic policy uncertainty, oil price volatility, and post-pandemic economic instability have created significant challenges for the Islamic banking industry, particularly in Organization of Islamic Cooperation (OIC) countries. This study aims to examine the influence of geopolitical risk (GPR), economic policy uncertainty (EPU), world oil prices (WTI), inflation, and economic growth (GDP) on the profitability of Islamic banks measured by Return on Assets (ROA). This research employs a quantitative approach using balanced panel data from 20 Islamic banks across 10 OIC countries during the 2020–2024 period, consisting of 100 observations. Data were collected from annual reports, Bloomberg, World Bank, U.S. Energy Information Administration (EIA), Caldara and Iacoviello’s GPR Index, and Baker et al.’s EPU Index. The analysis method uses panel data regression through Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with model selection conducted using Chow, Hausman, and Lagrange Multiplier tests.The results show that REM is the most appropriate model. Geopolitical risk and inflation have a positive and significant effect on ROA, while world oil prices negatively and significantly affect ROA. Meanwhile, EPU and GDP growth do not significantly influence Islamic bank profitability.This study implies that Islamic banking demonstrates relatively strong resilience against global uncertainty due to its asset-backed financing and risk-sharing principles, thereby strengthening the role of Islamic finance as a stabilizing force in the financial system of OIC countries.